Imprinted electrodes for enhanced light trapping in solution processed solar cells - Mihi, Agustin; Beck, Fiona J.; Lasanta, Tania; Rath, Arup Kumar; Konstantatos, Gerasimos (Advanced Materials, 2013)

Determination of carrier lifetime and mobility in colloidal quantum dot films via impedance spectroscopy - Rath, Arup Kumar; Lasanta, Tania; Bernechea, Maria; Diedenhofen, Silke L.; Konstantatos, Gerasimos (Applied Physics Letters, 2014)
Impedance Spectroscopy (IS) proves to be a powerful tool for the determination of carrier lifetime and majority carrier mobility in colloidal quantum dot films. We employ IS to determine the carrier lifetime in PbS quantum dot Schottky solar cells with Al and we verify the validity of the technique via transient photovoltage. We also present a simple approach based on an RC model that allows the determination of carrier mobility in PbS quantum dot films and we corroborate the results via comparison with space charge limited measurements. In summary, we demonstrate the potential of IS to characterize key-to-photovoltaics optoelectronic properties, carrier lifetime, and mobility, in a facile way. (C) 2014 AIP Publishing LLC.

Remote trap passivation in colloidal quantum dot bulk nano-heterojunctions and its effect in solution-processed solar cells - Rath, Arup Kumar; Pelayo Garcia de Arquer, F.; Stavrinadis, Alexandros; Lasanta, Tania; Bernechea, Maria; Diedenhofen, Silke L.; Konstantatos, Gerasimos (Advanced Materials, 2014)
More-efficient charge collection and suppressed trap recombination in colloidal quantum dot (CQD) solar cells is achieved by means of a bulk nano-heterojunction (BNH) structure, in which p-type and n-type materials are blended on the nanometer scale. The improved performance of the BNH devices, compared with that of bilayer devices, is displayed in higher photocurrents and higher open-circuit voltages (resulting from a trap passivation mechanism).